h - Murgante, Beniamino; Misra, Sanjay; Carlini, Maurizio; Torre, Carmelo M.; Nguyen, Hong-Quang.; Taniar, David; Apduhan, Bernady O.; Gervasi, Osvaldo; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The five-volume set LNCS 7971-7975 constitutes the refereed proceedings of the 13th International Conference on Computational Science and Its Applications, ICCSA 2013, held in Ho Chi Minh City, Vietnam in June 2013. The 248 revised papers presented in five tracks and 33 special sessions and workshops were carefully reviewed and selected. The 46 papers included in the five general tracks are organized in the following topical sections: computational methods, algorithms and scientific applications; high-performance computing and networks; geometric modeling, graphics and visualization; advanced and emerging applications; and information systems and technologies. The 202 papers presented in special sessions and workshops cover a wide range of topics in computational sciences ranging from computational science technologies to specific areas of computational sciences such as computer graphics and virtual reality.
Computational Methods, Algorithms and Scientific Applications -- High-Performance Computing and Networks -- Geometric Modeling, Graphics and Visualization; Advanced and Emerging Applications -- Information Systems and Technologies.
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer software; Data mining; Computer simulation; Computer Science; Computer Communication Networks; Algorithm Analysis and Problem Complexity; Software Engineering; Simulation and Modeling; Information Systems Applications (incl. Internet).; Data Mining and Knowledge Discovery